Multiple inclined edge cracks in two bonded half-planes subjected to normal stress - Husin, Nur Hazirah; Nik Long, Nik Mohd Asri; Senu, Norazak; Hamzah, Khairum (Semarak Ilmu Publishing, 2025)
This paper considers multiple inclined edge cracks under normal stress originating at the interface of two bonded half-planes. The crack problem is formulated into the singular integral equation (SIE) using a modified complex potential (MCP) with the conditions of continuity for traction and displacement. A semi-open quadrature approach is applied for the numerical solution of the SIE. The behavior of stress intensity factors (SIFs) for both Modes I and II at all crack tips is computed and demonstrated graphically. The crack configuration, the elastic constant ratios of the planes, the inclination angle, and the distance between cracks have significantly influenced Modes I and II SIFs. By analyzing the behavior of SIF near the crack tip, engineers may predict the lifespan of the building structures.